Digital Halal Logistics: The Perspective of Food Delivery Riders (School of Business and Management Institut Teknologi Bandung, 2022)
Abstract. The growing awareness of Halal compliance in today’s community shows the importance of Halal on the quality of products manufactured worldwide. Hence, it is crucial to ensure that the concept of Halal extends to the entire supply chain, from the farm to the consumer. Most research covers manufacturing and procurement, leaving Halal-compliant distribution and logistics open to a number of research opportunities. We conduct an investigation into digital Halal logistics from the perspective of the individual food delivery riders, focusing on the operational level of the supply chain. The extensive reliance on Internet-enabled smart phones and the growing popularity of food delivery have created an increasing number of job opportunities for delivery riders, mainly on motorcycles. However, there is a question around whether or not this delivery process is Halal compliant, given that the riders face many challenges in ensuring an acceptable quality of service. This study investigates how the riders perceive Halal compliance in the food delivery industry, and provides suggestions for the implementation of digital Halal at various operational checkpoints. Keywords: Digital logistics, Halal logistics, supply chain management, delivery riders.